Use of Discriminant Technique to Classify Ground Water From Different Aquifers-A Case Study of Nagaur District - Chattergi, P C; Gupta, B S; Taimni, Vishnu (Annals of Arid Zone, 2016)
An attempt has been made to use Fisher’s linear discriminant function to differentiate between aquifer types and between individual aquifers of the same type under different physiographic settings. The principal ionic composition of ground water from different aquifer types was subjected to the analysis. Fisher’s linear discriminant function was found significant at I per cent probability level. Mahalanobis-D2 technique was applied to study the relative contribution of each characteristics in discriminating between two aquifers.